2007
DOI: 10.1017/s000748530700507x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation among Mediterranean populations ofSesamia nonagrioides(Lepidoptera: Noctuidae) as revealed by RFLP mtDNA analysis

Abstract: Restriction fragment length polymorphism analysis of two segments of mitochondrial DNA (COI and 16S rRNA) was used to examine genetic variation in Sesamia nonagrioides (Lefèbvre) populations from the Mediterranean basin. Four populations were collected from central and southern Greece, and five from northern latitudes: Greece, Italy, France and Spain. No variation was observed in COI, while 16S rRNA segment proved highly polymorphic and 28 different haplotypes were found. Lower intra-population polymorphism wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…The absence of significant Fu's F s east of the Alps may be attributed to the scarcity of sample locations that did not enable comparison of southern versus northern diversity, which was possible only west of the Alps, between Spain and France. However, Margaritopoulos et al . (2007) showed that an expansion occurred also east of the Alps, and that northern populations were less diversified than southern ones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of significant Fu's F s east of the Alps may be attributed to the scarcity of sample locations that did not enable comparison of southern versus northern diversity, which was possible only west of the Alps, between Spain and France. However, Margaritopoulos et al . (2007) showed that an expansion occurred also east of the Alps, and that northern populations were less diversified than southern ones.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of significant Fu's Fs east of the Alps may be attributed to the scarcity of sample locations that did not enable comparison of southern versus northern diversity, which was possible only west of the Alps, between Spain and France. However, Margaritopoulos et al (2007) showed that an expansion occurred also east of the Alps, and that northern populations were less diversified than southern ones. The evolution rate of 1.15% per Myr in Africa is hypothetical, although it is common in insects, and was deducted from the fact that it could explain the similar genetic distances between the infra-specific clades in many species of African Sesamiina by the influence of major paleoclimatic events.…”
Section: Time Of Birth Of the Palearctic Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent mitochondrial DNA (mtDNA) studies of Lepidopteran species with distribution ranges in Europe have reported no or low levels of genetic structuring in relation to distance between sample sites (e.g. Vandewoestijne et al , 2004; Margaritopoulos et al , 2007). Red admirals are much more mobile than these species.…”
Section: Introductionmentioning
confidence: 99%
“…This pest has been traditionally regarded as a rather sedentary pest , Eizaguirre et al 2004, Margaritopoulos et al 2007), likely to develop genetic isolation between geographical regions. Genetic differentiation between S. nonagrioides populations in European countries has been reported using different molecular markers (Bues et al 1996, Kourti 2006, Leniaud et al 2006, Margaritopoulos et al 2007, De La Poza et al 2008. reconstructed the evolutionary history of Palaearctic and Sub-Saharan populations of S. nonagrioides using one nuclear and two mitochondrial genes and concluded that the isolated Iranian population appears to have recently originated from a population of eastern Europe origin.…”
Section: Introductionmentioning
confidence: 99%